Motivasi Tinggi Meningkatkan Minat Mahasiswa Untuk Melanjutkan Profesi Ners - Rosdiana, Yanti; Hastutiningtyas, Wahidyanti Rahayu; Putri, Ronasari Mahaji (Universitas Tribhuwana Tunggadewi, 2019)
Nursing students can only be said to be professional if the student has continued professional if the student has continued professional profession education, but unfortunately there are still many students who are not willing to continue to the level. Student motivation in one way to bring out, move, desire and direct behaviour. Such behaviour will form an activity of its own to determine the relationship of motivation with the interest of students to continue profession professions at Tribhuwana University Tunggadewi Malang. This research uses analytic observation design with cross sectional approach. The population in this study were all Nursing science study Program students at the Tribhuwana Tunggadewi University in Malangwho would continue the profession of nurses. The sampling technique used in this study was a total sampling of 87 respondents. The dependent variable in this study in the independent interest and variable, namely motivation. Data were collected using a modified questionnaire, namely interest with IIQ (The Individual Interest Questionnaire) and motivation with Motivation Quuestionnaire Aspira. Data were performed using SPSS. Spearman-rank test results obtained p value = (0,000) (0,050) with a positive value of r (correlation coefficient) 0,391 wich means that there is a significant relationship of motivation with interest. Thus the higher the motivation will increase the interest of studets to continue professional education nurse, so it is hoped that there needs to be an early introduction to the Ners professional education program to increase motivation with the interest of nursing students of continue professional ners education